1989
DOI: 10.1042/bj2640813
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-mediated endocytosis and nuclear transport of human interleukin 1 α

Abstract: In this study we demonstrate that 125I-labelled interleukin (IL) 1 alpha binds specifically to its receptor on the surface of EL4 6.1 cells and is subsequently endocytosed and translocated from the cell membrane to the nucleus, where it progressively accumulates. Two-dimensional polyacrylamide-gel electrophoresis revealed that the internalized 125I-IL1 alpha associated with the nucleus was intact, with negligible breakdown products present. Specific and saturable binding of 125I-IL1 alpha was demonstrated on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 61 publications
1
37
0
1
Order By: Relevance
“…Indeed, the microarray data revealed that IL-37 acts as an inhibitor of TLR and IL-1-mediated pathways, which confirms earlier findings 21 . Besides extracellular binding, IL-37 has been shown to translocate to the nucleus where it may act as a transcriptional modulator 28 , as is the case with nuclear translocation of another member of the IL-1 family member IL-1a 51,52 . Altogether, these mechanisms probably account for the anti-inflammatory actions of IL-37 in the adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the microarray data revealed that IL-37 acts as an inhibitor of TLR and IL-1-mediated pathways, which confirms earlier findings 21 . Besides extracellular binding, IL-37 has been shown to translocate to the nucleus where it may act as a transcriptional modulator 28 , as is the case with nuclear translocation of another member of the IL-1 family member IL-1a 51,52 . Altogether, these mechanisms probably account for the anti-inflammatory actions of IL-37 in the adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of cytokine receptors through internalisation can help to decrease the beta cell toxicity of proinflammatory cytokines. Internalisation of the IL-1β receptor has been described in different cell types, where the internalised receptor accumulated in the cytosol and could be recycled to the plasma membrane [70,71,72]. Receptor-mediated endocytosis was also shown for IFN-γ, but in contrast to the recycling of the IL-1β receptor, a lysosomal ligandreceptor degradation occurred after internalisation [73].…”
Section: Discussionmentioning
confidence: 99%
“…10 (3) Both IL-1 and TNF-␣ have been shown to be internalized by a receptor-mediated process. 44,45 Suppression of TNF-␣-mediated E-selectin expression by PAO has been attributed to an inhibition of receptor-mediated endocytosis of TNF-␣. 30 Whether this mechanism can explain the observations with IL-1 remains to be established.…”
Section: Discussionmentioning
confidence: 99%